The Impact of Terrorism on Governance in African Countries - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2017)
This study investigates how terrorism affects governance in 53 African countries for the period 1998-2012. Four terrorism indicators are used namely: domestic, transnational, unclear and total terrorism. Ten bundled and unbundled governance indicators are also employed namely: political governance (consisting of political stability and voice and accountability), economic governance (encompassing government effectiveness and regulation quality); institutional governance (entailing corruption-control and the rule of law) and general governance. The governance indicators are bundled by means of principal component analysis. The empirical evidence is based on Generalized Method of Moments. Three key findings are established. First, all selected terrorism dynamics negatively affect political governance and its constituents. Second, evidence of a negative relationship is sparingly apparent in economic governance and its components. Third, no proof was confirmed in relation to the impact of terrorism and institutional governance with its elements. Fourth, compared with domestic terrorism, transnational terrorism more negatively and significantly affects political, economic and general governances. Policy implications are discussed.
Keywords: C52; D74; F42; O38; P37; 330; Terrorism; Governance; Africa